Knowledge and Husband's Support with Exclusive Breastfeeding in Lubuklinggau City, Indonesia - Suryani, Suryani; Khairani, Nurul; Hendriyani, Hendriyani (Diversity: Disease Preventive of Research Integrity, 2022)
The provision of breastmilk for newborns is one of the efforts to prevent death and malnutrition in infants and toddlers. This study aimed to determine the relationship of the husband's knowledge and support with breastfeeding in Lubuklinggau City. This type of research was an analytical survey research with a cross-sectional design. The sampling technique used was random sampling to obtain a sample of 60 mothers. Data collection used primary data in the form of a questionnaire designed to test the mother's knowledge and husband's support. The data analysis technique was univariate and bivariate analysis with Chi-Square statistical test. The results showed that from 60 mothers, there were 22 mothers (36.7%) who had good knowledge, 34 mothers (56.7%) who supported their husbands well, and 32 mothers (53.3%) who exclusively breastfed their babies. This study found a significant relationship between husband's knowledge and support with exclusive breastfeeding in Lubuklinggau City with a moderate category. This provides information that to increase the mother's role in breastfeeding, and it needs to be supported by adequate knowledge about the benefits of breastfeeding for babies and family support, especially the husband as the closest person to the mother. This study recommends the importance of promoting exclusive breastfeeding for infants from various media and increasing the activity of posyandu cadres in providing information about exclusive breastfeeding.